Media Pembelajaran Video Simulasi Perubahan Wujud Zat dan Bentuk Energi: Penelitian dan Pengembangan - Risma Anggreini; Eva Nurul Malahayati; Adin Fauzi (Concept: Journal of Social Humanities and Education, 2024)
IPAS (Social and Exact Science Education) is a subject in the Kurikulum Merdeka. This subject invite student to recognize natural anomalies by facts. However, results of the researcher's observations on the interest of 4th-grade elementary school students in learning science showed that 93.75% of students experienced difficulties in learning science, especially in the matter of changes in the state of matter and energy forms. So, based on the results of the theoretical formulation and potential problems, the researcher is interested in proposing the development of a simulation video product. This type of research is Research and Development (R&D) based on 7 stages, namely, potential and problems, data collection, product design, design validation, design revision, product testing, and product revision due to limitations of materials, time, and manpower. After the prototype product is completed, the researcher validates the content, media, and language with 9 experts, with each having 3 validations: (Content validators, Media validators, Language validators) The test results show that 86% of the material validation, 92% of the media expert validation, and 96% of the language validation, it can be concluded that the simulation video product is very feasible to use with minor revisions. Furthermore, the researchers carried out a teacher and student readability test on the simulation video media. The scores obtained were 91,2% for teachers and 89,2% for students. So that simulation video products able as media supplements in learning.